Summation of reciprocals related to quintuple product of generalized fibonacci sequences - Gaowen, Xi, (Utilitas Mathematica, 2011)
By applying the method of generating function, the purpose of this paper is to give several summations of reciprocals related to quintuple product of generalized Fibonacci sequences.As applications, some identities involving Fibonacci, Lucas numbers are obtained.